The Prospects of Operational Search Activity in Digital Environment - Gafurov Ikromjon Ilxomovich (Web of Journals Publishing, 2023)
This article is devoted to the analysis of operational-search activities in the context of the modern digital environment. In the context of the rapid development of information technologies and the widespread use of digital platforms, operational-search activity is acquiring new aspects and challenges. The article discusses key aspects of such activities, including technical tools, legal and ethical issues, privacy and data protection. The authors analyze the impact of the digital environment on the operational-search activity and outline the prospects for its development in this context.
Keywords: Operational-search activity, digital environment, information technology, data privacy, legal aspects.